Inter-play of religion, politics, and communalism in India - Prabhakar, Samson; Prabhakar, Samson (Bangalore : BTESSC/SATHRI, 2004)
Contributed articles, some presented as papers in a national level consultation at Whitefield, England, in October 2003.
Keywords: Religion and politics; Communalism